Piper Betle Leaves Extract As A Green Corrosion Inhibitor For Aluminium In Acidic Medium Characterization And Evaluation Of Antioxidant, Phenolic And Flavonoid Content - Navieen, Murugaiah (Universiti Sains Malaysia, 2022)
The aluminium (Al) is one of the most utilized metals in various industries such as chemical, mechanical, aerospace and among others. However, the corrosion occurs in the Al due to aggressive environment such as highly acidic or alkaline medium remain as unavoidable phenomena. There are numerous methods are explored and implemented to avoid the corrosion of Al in the aggressive medium. The usage of natural products like plant extract as a corrosion inhibitor is the most sustainable and eco-friendly method to prevent the corrosion in the Al. In this research, the Piper Betle leaves extract (PBLE) was chosen as a green corrosion inhibitor for Al in hydrochloric acid (HCl) solution. The Piper Betle leaves were extracted by using ultrapure water which was affordable, environmentally friendly and high solubility compared to other solvents. This extraction method was simple and low cost. The inhibitive properties of PBLE on Al surface in 1.0M HCl solution was determined by gravimetric measurement which was known as weight loss method. The concentration of PBLE and immersion duration of Al in HCl solution with absence and presence of PBLE parameters were analyzed in this research. The range of PBLE concentrations utilized in this research was from 50 mg/L to 1000 mg/L while the range of immersion period of Al in absence and presence of PBLE was from 1 hour to 24 hours. The maximum inhibition efficiency of PBLE was 94.41% on Al surface in 1.0M HCl solution containing inhibitor concentration of 1000 mg/L at room temperature for 1 hour. The gravimetric analysis showed that the inhibition efficiency gradually increases with increasing inhibitor concentrations while it decreases with increasing Al immersion duration. The Fourier-Transform Infrared Radiation (FTIR) characterization confirmed that the existence of hydroxyl (-OH), carboxylic acid and polyphenol groups in PBLE molecule prevent the corrosion process on Al surface in acidic medium. On the other hand, the Scanning Electron Microscopy (SEM) analysis showed the PBLE molecules formed a barrier or layer on Al surface to inhibit the corrosion in the acidic solution. The total phenolic content (TPC) and flavonoid content (TFC) of PBLE were 64.87 mg/g of gallic acid and 120.39 mg/g of quercetin, respectively, indicated that the PBLE molecules contain higher antioxidant properties which can terminate the corrosion reaction on Al surface in acidic environment. In addition, the inhibition occurred via adsorption of PBLE molecules on the Al surface obeyed Langmuir isotherm model. The calculated adsorption free energy (